Long-Term Outcomes (2 Years) After Hyaluronic Acid Therapy for Peyronie’s Disease - Cocci, Andrea; Di Mauro, Marina; Kluth, Luis; Capogrosso, Paolo; Falcone, Marco; Mondaini, Nicola; Russo, Giorgio Ivan (Frontiers in Urology, 2022)
Background: Hyaluronic acid (HA) has demonstrated clinical benefits for the treatment of Peyronie’s disease (PD), however there are no reports that documented long-term outcomes. The aim of the current study is to illustrate the clinical outcomes after two years of follow-up in patients that received HA for PD. Methods: From January 2015 to December 2018, we enrolled 244 patients affected by PD in this multicenter non-randomized clinical study, as previously reported. Patients received intralesional HA (Group A) or verapamil (Group B). Follow-up was undertaken after three months, one- and two-years. International Index of Erectile Function (IIEF-5), PC and visual analogue scale (VAS) were collected. Results: Among the whole cohort, 125 patients were included in Group A and 119 in Group B. As PC, the median curvature was 25.0° at 3-months (IQR: 15.0-30.0) (p=0.45) and it was maintained at 1- (p=0.87) and 2-year of follow-up (p=0.90) (Group A) while it was 30.0° (IQR: 20.0-35.0) (p=0.67) at three-months and it was stable at 1- (p=0.77) and 2-year of follow-up (p=0.80)(Group B). For VAS score, the median change in Group A was -4.0 (IQR: -4.0, -5.0, p<0.01) after 3-months, -4.0 (IQR: -4.0, -5.0, p<0.01) at 1- and -4.0 (IQR: -4.0, -5.0, p<0.01) at 2-years of follow-up, while in Group B it was -1.0 (IQR: -2.0, -0.5, p=0.25) after 3-months, -3.5 (IQR: -3.5, -2.0, p<0.01) at 1- and -4.0 (IQR: -4.0, -5.0, p<0.01) at years of follow-up. Adjusted p-value for between-group comparisons was <0.01 at 3-months and not significant at 1- (p=0.53) and 2 years (p=0.80). Conclusions: We reported clinical efficacy of intralesional HA in patients with PD after two years of follow-up by slightly improving penile curvature (PC) and bother of the disease. These results should be considered during the counselling of the patients especially regarding the lack of worsening during the time.